2011
DOI: 10.1200/jco.2010.31.3577
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Array Analysis Identifies Profiles of Blood-Derived DNA Methylation Associated With Bladder Cancer

Abstract: A B S T R A C T PurposeEpigenetic alterations in tissues targeted for cancer play a causal role in carcinogenesis. Changes in DNA methylation in nontarget tissues, specifically peripheral blood, can also affect risk of malignant disease. We sought to identify specific profiles of DNA methylation in peripheral blood that are associated with bladder cancer risk and therefore serve as an epigenetic marker of disease susceptibility. MethodsWe performed genome-wide DNA methylation profiling on participants involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 39 publications
4
99
1
Order By: Relevance
“…Other uses might follow, and they will require further development, such as our finding of a distinct DNA methylation fingerprint between local liver metastases and distant brain metastases derived from colorectal tumors that might suggest the use of DNA methylation patterns to predict the metastatic spectrum of a given cancer. We would also like to highlight another promising step in the clinical-benefits direction by the recent finding of 27,000 CpG-site DNA methylation profiles in blood that are associated with bladder cancer risk (Marsit et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other uses might follow, and they will require further development, such as our finding of a distinct DNA methylation fingerprint between local liver metastases and distant brain metastases derived from colorectal tumors that might suggest the use of DNA methylation patterns to predict the metastatic spectrum of a given cancer. We would also like to highlight another promising step in the clinical-benefits direction by the recent finding of 27,000 CpG-site DNA methylation profiles in blood that are associated with bladder cancer risk (Marsit et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hypermethylation of BRCA1 is reportedly associated with increased prevalence of BRCA1-methylated breast tumors (65,66), suggesting a functional link between blood detectable DNA methylation and disease histology (67)(68)(69). High-throughput discovery studies have identified cancerassociated DNA methylation signatures in blood of patients with breast (69), ovarian (68), bladder (67), and head and neck cancers (70), providing potential cancer diagnostic biomarkers.…”
Section: Dna Methylation Variability and Cancer Riskmentioning
confidence: 99%
“…10 Given the accessibility of methodology, 11,12 genome-wide methylation analyses have been extended to peripheral blood in case-control studies of ovarian, bladder and head and neck cancers. [13][14][15] A few aberrant methylation patterns in peripheral blood have also been reported in BC by candidate gene approaches. [16][17][18][19] Recently, Xu et al reported an extensive blood-based epigenome-wide association study of BC by Illumina 27K Methylation Array in a well-designed prospective sister study cohort, and demonstrated that the methylation profiling of blood are promising markers for BC detection and risk evaluation.…”
mentioning
confidence: 99%